METHODS OF USING GENDER CHARACTERISTICS IN SOCIAL ADVERTISING CREATED IN UZBEK AND ENGLISH LANGUAGES - Bektoshev Otabek Kodiraliyevich; Mahmudova Nigora Boyquzi qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Based on the analysis and research factors of this research work, it can be said that advertising that attracts human attention and aims to influence him intensively requires constant change, because any means of influence become obsolete over time. As a result, it loses its previous attractiveness, attractive features, in a word, liveliness, as a result of which the persuasiveness of advertising weakens. It is worth noting that in social advertisements created in Uzbek and English languages, the text of the advertisement is important in the use of linguistic means, and it is characterized by the tendency to use linguistic means to the maximum extent.